Law as a Gift and Reciprocal Gift of the Monarch in the Grand Duchy of Lithuania (on the Example of the 1447 Common Noble Privilege). - Polishchuk, Volodymyr (Vilnius University Open Series, 2024)
The article analyzes the concept of “gift”, which is considered in the categories of mentality, through the concept of “legal consensus”, using the preamble of the common noble privilege of Casimir in 1447 as an example. The study combines diplomatic, semantic and structural anthropological approaches to read and interpret the legal act. The “gift” is considered as an element of the common language between the ruler and the subjects of the GDL. The terms “donatio” and “recompensatio” are analyzed in detail. The preamble of the common noble privilege justifies the granting of noble rights by the monarch as a reward for the gifts of his lordship (“доброты, ласкы и дары”/“bono, graciarum et libertatum”). The anthropological understanding of the phenomenon of “gift” as a phenomenon of the customary culture of the late medieval and early modern society of the GDL becomes important. Some issues of translation of latin legal monuments into ruthenian are considered.
Keywords: Grand Duchy of Lithuania; the common noble privilege of 1447; “gift” (donatio i recompensatio); legal consensus; noble rights